100 site analysis essentials : an architect's guide - Farrall, Peter; Jackson, Iain (London : RIBA Publishing, 2024)
How do I follow a brief? What is the site's context? What's its history and what is adjacent to it now? How have other designers responded to similar site conditions? Conducting a site analysis is an essential part of the design process. Through careful examination, observation and documentation, you can cultivate a deeper understanding of the place you are designing. Designed to help students understand what a 'site analysis' is and why it is valuable to their design proposals, this book provides 100 easy-to-follow rules of thumb with simple line drawings and illustrations to help. Through a series of lenses, strategies and ideas, this book provides step-by-step guidance through the process to increase your understanding of a place and how to deliver the appropriate solution for your site. Supported by case studies with examples of tackling specific problems, you will develop the tools to explore, rationalise and convince others that your approach is right for the project.
Keywords: Building sites -- Planning -- Handbooks, manuals, etc; Architecture -- Handbooks, manuals, etc; ARCHITECTURE / Methods & Materials; ARCHITECTURE / General